Fear, intolerance, resignation: some readings on contemporary immigration in Italy (Tempo e Argumento, 2021)
Several studies have shown how fear and anxiety are emotions that have marked contemporary society, with new and old triggers of these feelings affecting subjects in today’s world. The other, otherness, has been an object of concern, fear, in various human collectivities over time. With regard to migratory processes, we notice how this fear of what is different has constructed stereotypes, walls, intolerance, feelings that are often hidden in the idea of ​​‘integration,’ i.e. in the search to annul what characterizes the other, within the host society. On the other hand, in the migrant person, the search for ‘integration’ can show – differently – a resignation that marks an effort to gain acceptance and recognition. This article aims to analyze – relying on the oral history methodology – the phenomenon of contemporary immigration in Italy, with an emphasis on people from Latin America, seeking to grasp the resources used by these individuals to be ‘approved’ in the context of the land of arrival. Thus, the break of a chain of distrust, built as a consequence of a socially shared fear, would enable an inclusion process, i.e. the insertion of the other in the host community, with no need to divest from oneself.Keywords: Latin American migration; contemporary Italy; sensibility; memory; social inclusion.